Answer:
(1) First pair; (2, 3), (7, 3), d₁ = 5
(2) Second pair; (-2, 5), (-2, -3), d₂ = 8
(3) Third pair; (-8, 5), (-2, 5), d₃ = 6
(4) Fourth pair; (-9, 1), (6, 1), d₄ = 15
Explanation:
Given pair of points;
(1) (2, 3), (7, 3)
(2) (-2, 5), (-2, -3)
(3) (-8, 5), (-2, 5)
(4) ) (-9, 1), (6, 1)
The distance between each pair of points is calculated as follows;
![d = √((y_2-y_1)^2 + (x_2-x_1)^2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/nakd7t6gnirgb405sudf7rnz0q6i7xvi6q.png)
(1) first pair; (2, 3), (7, 3)
![d_1 = √((3-3)^2 + (7-2)^2) \\\\d_1 = 5](https://img.qammunity.org/2022/formulas/mathematics/high-school/qzk9ze6t2vk38osuwy0fz3blrywrpl1qd6.png)
(2) second pair; (-2, 5), (-2, -3)
![d_2 = √((-3-5)^2 + (-2-(-2))^2)\\\\d_2 = √((-3-5)^2 + (-2+2)^2) \\\\d_2 = 8](https://img.qammunity.org/2022/formulas/mathematics/high-school/slwn6mj9wu80ks1nr8gpqgcx52xhbivp8a.png)
(3) Third pair; (-8, 5), (-2, 5)
![d_3 = √((5-5)^2 + (-2-(-8))^2)\\\\d_3 = √((5-5)^2 + (-2+8)^2) \\\\d_3 = 6](https://img.qammunity.org/2022/formulas/mathematics/high-school/lhfqsoa6flhi6b5hnkbh5br8e59y6zya2i.png)
(4) Fourth pair; (-9, 1), (6, 1)
![d_4 = √((1-1)^2 + (6-(-9))^2)\\\\d_4 = √((1-1)^2 + (6+9)^2) \\\\d_4 = 15](https://img.qammunity.org/2022/formulas/mathematics/high-school/g87e3ptd3i7ct8eok3b47qpa6okx6xfpa8.png)